An algorithm for job scheduling in 2 - machine flow shop problem (2009)
This paper considers the problem of scheduling in flow-shop by Johnson's Algorithm method and Genetic Algorithm method to find an optimal sequence for n jobs machine problem based on minimum elapsed time. In scheduling the two machine flow shop problem F2||∑C1, one has to determine a schedule that minimizes the sum of finishing times of an arbitrary number of jobs that need to be executed on two machines, such that each job must complete processing on machine 1 before starting on machine 2. We propose a heuristic for approximating the solution for the F2||∑C1 problem using a genetic algorithm.